The Effect of Work Experience and Hard Skill on Employee Performance of PT. Multi Kencana Niagatama - Mokhamad Nurdin (At-Tadbir : jurnal ilmiah manajemen, 2023)
Workers who have been on the job for a while have amassed a wealth of experience and are therefore expected to possess a diverse set of abilities. The study's objective was to determine the value of prior job experience and specialized training in improving productivity in the workplace. Quantitative verification is utilized. The total number of participants in this study was 126. Multi Kencana Niagatama Tbk. One hundred PT. Multi Kencana Niagatama staff members were recruited for the study. The research sample was selected using a random sampling strategy. One hundred PT Multi Kencana Niagatama workers were surveyed using a questionnaire. The smart PLS 3.0 software was used to analyze the research data. The study found that work experience significantly (p<0.05) influenced employee performance, that hard skills significantly (p<0.05) influenced employee performance, and that work experience significantly (p<0.05) influenced employee performance through the mediation of hard skills. Thus, employees' productivity is influenced by their job experience and concrete talents. It is hoped that future study would yield a performance escalation paradigm for fostering the competitive growth of employees' hard talents for the benefit of the business.